Smart Home Pengendali Lampu Rumah Berbasis SMS Gateway dan Arduino Menggunakan Smartphone Android - Khairil Anam (Department of Science and Technology Ibrahimy University, 2020)
Control of electrical equipment using this mobile phone is a tool used by humans to make it easier to do work done over and over again, such as turning off / turning on the lights at a distance. This tool is made to make it easier for us to control the lights of the house, if left far away, the media used is a mobile phone by utilizing SMS facilities. This tool consists of one Arduino UNO for storing programming and as a system brain, SIM800L V2 for receiving and sending SMS to simcard numbers, Relay for turning off / on lights, 16x2 LCD to display predetermined words such as when sending SMS or when turning on the system, a piece of breadboard to connect some jumper cables to make it look neat, and the lights. This light control system will work according to a predetermined program, then this microcontroller will receive an SMS from the cellphone number used to control the system. In this study, the discussion is a house light control system with SMS gateway.